2006
DOI: 10.1007/s10495-006-9236-3
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of eukaryotic cell apoptosis by members of the bacterial order Actinomycetales

Abstract: Apoptosis, or programmed cell death, is normally responsible for the orderly elimination of aged or damaged cells, and is a necessary part of the homeostasis and development of multicellular organisms. Some pathogenic bacteria can disrupt this process by triggering excess apoptosis or by preventing it when appropriate. Either event can lead to disease. There has been extensive research into the modulation of host cell death by microorganisms, and several reviews have been published on the phenomenon. Rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…The induction of host cell apoptosis in response to a bacterial pathogen can be considered from two perspectives: as a virulence mechanism of the pathogen or as a defence mechanism of the host55. Most research indicates that the apoptosis of macrophages infected with mycobacteria functions as a host defence mechanism to eliminate the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of host cell apoptosis in response to a bacterial pathogen can be considered from two perspectives: as a virulence mechanism of the pathogen or as a defence mechanism of the host55. Most research indicates that the apoptosis of macrophages infected with mycobacteria functions as a host defence mechanism to eliminate the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies showed that N. asteroides strain GUH-2 was neuroinvasive in the brains of mice [44], [45] and monkeys [46] and that infection resulted in apoptotic death of DA neurons associated with proteasome inhibition [47], [48]. Another nocardial strain (GAM-5) has also been shown to induce impaired movements and similar pathological features in mice following sublethal infection [49].…”
Section: Discussionmentioning
confidence: 99%
“…These phenotypes are capable of undergoing dedifferentiation, transdifferentiation, and apoptosis depending on the stimulus (Barry & Beaman 2006). These changes are orchestrated by a range of neurons and cytokines secreted into the damaged environment and SC autocrine factors.…”
mentioning
confidence: 99%